Changes in handgrip force and blood lactate as response to simulated climbing competition - Gajewski, J.; Hübner-Wozniak, E.; Tomaszewski, P.; Sienkiewicz-Dianzenza, E. (Biology of Sport, 2009)
The aim of the study was to estimate post-competition changes in handgrip strength and blood lactate in climbers and relationships of the studied variables with declared climbing ability of the tested athletes. Twenty one male climbers volunteered to take part in the experiment. Each subject took part in simulated lead climbing competition on the artificial wall - (difficulty 7a in French scale). The blood lactate concentration was measured pre-climbing and then 3 min and 30 min post-climbing. Grip force of both hands (dominant and non-dominant) was measured twice - pre-climbing and 1 min post-climbing (semi-final). Maximum heart rate during climbing reached 181.4±7.7 beats per minute. Lactate concentration amounted to 6.35±1.50 mmol/1 and 2.28±0.66 mmol/1 3 min and 30 min post-climbing, respectively. Handgrip force related to body mass (averaged for both hands) decreased significantly from 7.39±1.30 N/kg pre-climbing to 6.57±1.05 N/kg 1 min post-climbing. Self reported climbing ability was correlated with lactate concentration and handgrip force, as well. It was demonstrated that athletes reporting higher climbing ability showed better lactate recovery.